4-Benzyl-6-bromo-2-(4-methoxyphenyl)-4H-imidazo[4,5-b]pyridine monohydrate - Ouzidan, Y.; Rodi, Y.K.; Obbade, S.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The imidazopyridine fused ring in the title compound, C(20)H(16)BrN(3)O center dot H(2)O, is coplanar with the aromatic ring at the 2-position [dihedral angle = 5.2 (1)degrees]. In the five-membered imidazo portion, the C-N bond whose C atom is also connected to the pyridine N atom has predominantly double-bond character [1.334 (2) angstrom] whereas the C-N bond whose atom is connected to the pyridine C atom has predominantly single-bond character [1.371 (2) angstrom]. The water molecule engages in hydrogen bonding with the latter N atom; it is also connected to a symmetry-related water molecule, generating a linear chain structure.